Analisis Minat Belajar Peserta Didik Terhadap Pembelajaran Matematika di Sekolah Dasar - Dwi Heri Murtiningsih; Kusmiyati Kusmiyati (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
Mathematics is a subject that has an important role for individuals, both in the realm of education and in the lives of these individuals, so it is necessary to conduct research to find out students'interest in learning mathematics. The purpose of this study was to find out and describe the interest in learning mathematics in 4th grade students of Al Mubarok Islamic Elementary School, Gunung Anyar, Surabaya. This type of research is quantitative descriptive with the research subjects being all 4th grade students with a total of 63 students. The data collection method used was by distributing questionnaires via Google form and direct observation. The results of this study prove that the learning interest of 4th grade students at Al Mubarok Islamic Elementary School is quite good with a percentage of 67.04%.